QARAQALPAQ TILI (MÁMLEKETLIK TIL) SABAǴÍNDA MASHQALALÍ TÁLIMNEN PAYDALANÍWDÍŃ BAZI BIR MÁSELELERI - Jaksımova, U.J. (SCIENCE and SOCIETY, 2017)
The article deals with the issues of using educational technologies in problem teaching at the lessons in «karakalpak language», the state language. The author also describes the aims, levels and peculiarities of theoretical bases of problem teaching.